Continuous stiffness assessment of cement-stabilised soils from early age - Silva, Jacinto (2013)
Recently, an innovative technique based on continuous modal identification of the first flexural resonant frequency of a simply supported composite beam has been proposed for continuous evaluation of the E modulus of concrete from the instant of casting (termed EMM-ARM: elasticity modulus measurement through ambient response method), and has been successfully compared with other existing techniques. In view of its potential applications for the laboratory and in situ characterisation of cement-stabilised soils, the extension of using EMM-ARM for these materials has been preliminarily tested with promising results, but the extension of the procedure has also resulted in the identification of new challenges. The purpose of this paper is to show the results and conclusions of an experimental programme devised to evaluate a sand–cement mixture from compaction to 28 days later by comparing several testing methodologies: EMM-ARM, unconfined cyclic compression tests, bender-extender elements, and ultrasonic contact probes. Attention is also given to the issue of obtaining in situ samples using the EMM-ARM technique through a specially designed mould.